The impact of remittance inflows on poverty in Botswana: An ARDL approach - Mercy. T. Musakwa; Nicholas M. Odhiambo (Journal of Economic Structures, 2019)
The growing pressure on governments to reduce poverty among other Sustainable Development Goals (SDGs) through harnessing domestic and foreign sources has motivated studies on the relationship between poverty and different economic variables in many developing countries. This study investigates the impact of remittance on poverty in Botswana, employing time-series data from 1980 to 2017. The study employs two poverty proxies-household consumption expenditure and infant mortality rate to capture poverty in its multidimensional form and improve the robustness of the results. Using the autoregressive distributed lag (ARDL) approach, the study finds that remittance inflows reduce poverty in Botswana-both in the short run and in the long run when infant mortality rate is used as a proxy. However, when poverty is measured by household consumption expenditure, remittance was found to have no impact on poverty in the short run and in the long run. The study, therefore, concludes that remittance inflows play a crucial role in reducing poverty and that Botswana can benefit immensely from the surge in remittance inflows by putting in place policies and structures that support remittance inflow.
Keywords: F24; I31; 330; Remittance; Poverty; Household consumption expenditure; Infant mortality rate; Botswana; ECM-based causality testing